“Teasing” and “mocking” as the language of courtship: The egalitarian gendered status of Lundayeh women - Kavitha Ganesan (Pusat Penataran IImu dan Bahasa, 2021)
This article examines the complementarity that exist between Lundayeh men and women by exploring the community’s oral literature to determine whether “teasing” and “mocking” can be perceived as forms of language courtship, and more importantly, how do such language forms in Lundayeh relationships provide the womenfolk a rather egalitarian gendered status in the community. By contextualizing the Lundayeh as both inlanders and highlanders of Borneo, this article employs two lines of inquiry: (1) the extent to which, as swidden hunter-gatherers, the sexual division of labor among the Lundayeh men and women contribute to the complementarity in gendered status; and, (2) how does the past practice of successful headhunting, that is celebrated through a commemorative ceremony, highlight the role of women as they make fun of the severed head, cry for the head, and eventually nurse the head, has been translocated as “teasing” and “mocking” in the community’s oral literature. The latter is important to locate the cultural significance of headhunting because, if the head was a symbol of male sexuality in the past, after the abolishment of headhunting during the colonial period and following conversion to Christianity, the present-day “teases” and “mocks” in the oral literature stand as a testament that men do not have access to the women until they prove their masculinity. This is to say that, even though headhunting has formally ended since the 1930s, the cultural significance associated with headhunting continues to survive in the oral literature, because, as the evidence suggest, women can utilize opportunities such as courtship or even pre-arranged alliances by manipulating the situation in order to both mock and relish their male partners.